2013
DOI: 10.1103/physrevb.87.155309
|View full text |Cite
|
Sign up to set email alerts
|

Defect-induced magnetism: Codoping and a prescription for enhanced magnetism

Abstract: Recent works have given indication that the defect induced magnetism in diluted magnetic semiconductors (DMSs), transition metal oxides (TMOs) and related materials is facilitated and enhanced by codoping and the synergistic action among the codopants. In the present work, we demonstrate that the proposed defect-induced ferromagnetic coupling (FMC) exhibits the following features; bipartition, synergy and locality and is based on the formation and interaction among spinpolarized neighborhoods analogous to spin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
45
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 59 publications
5
45
0
Order By: Relevance
“…Our results indicate that the magnetic coupling among the induced and/or doped magnetic moments takes the form of an interaction among spin polarized molecular units which is facilitated by the formation of the hosted bipartite codopant structures [1]. The universality of the proposed mechanism is further supported by earlier results referring to the rhombohedral C 60 -based polymers [2,3].…”
supporting
confidence: 82%
See 1 more Smart Citation
“…Our results indicate that the magnetic coupling among the induced and/or doped magnetic moments takes the form of an interaction among spin polarized molecular units which is facilitated by the formation of the hosted bipartite codopant structures [1]. The universality of the proposed mechanism is further supported by earlier results referring to the rhombohedral C 60 -based polymers [2,3].…”
supporting
confidence: 82%
“…Our work over the last three years has led to several publications in quality journals [1,2,3,4,5,6,7,8,9,10,11,12]. The expertise gained in the prior investigations will provide valuable insights, contributing to the success of the present project.…”
mentioning
confidence: 79%
“…As such, the saturation magnetization of (Co,Cu)-codoped ZnO films reasonably increases with increasing Co concentration below 10%. 43 demonstrated that a defect-induced ferromagnetic coupling with the features of bipartitioning, synergy, and locality is mediated by the molecular orbitals of these spin-polarized radicals. In their opinion, the origin of magnetism in DMSs and transition metal oxides appears to be the synergy and the interplay between correlated spin-polarization processes that take place independently within neighborhoods centered at the codopants.…”
Section: Discussionmentioning
confidence: 99%
“…[29]) with the result that the total magnetic moment, µ u−cell , is found to be either smaller or greater than 2µ T M (the sum of the magnetic moments of the two impurities). The former (and, correspondingly, the latter) case appears when the induced spin polarization on the anions leads to anion magnetic moments, µ S , with directions antiparallel (and, correspondingly, parallel) to that of the TM-impurities.…”
Section: Resultsmentioning
confidence: 99%
“…As demonstrated in our recent works, significant enhancement in the ferromagnetic coupling (FMC) among the magnetic dopants can be achieved for the diluted magnetic semiconductors (DMSs) and transition metal oxides (TMOs) by codoping [29,[33][34][35][36][37][38][39][40][41][42]. We attributed this enhancement to successive local spin-correlations of ferromagnetic type which act in opposition to the AFM superexchange coupling.…”
Section: B Codoped Systemsmentioning
confidence: 94%